Phosphorus and selenium compounding mitigates Cr stress in peanut seedlings by enhancing growth homeostasis and antioxidant properties - Yin, Hongliang; Jing, Yongping; Lin, Yunqing; Song, Ningning; Zong, Haiying; Wang, Fangli; Li, Shaojing; Song, Xin; Hou, Hong; Guan, Yuxian Shang; Zong, Quanli; Liu, Jun (Environmental science and pollution research international, 2024)
Peanut is an economically important crop, but it is susceptible to Cr contamination. In this study, we used peanut as experimental material to investigate the effects of exogenous P, Se interacting with Cr on the nutrient growth and antioxidant system of peanut seedlings by simulating Cr (0 μM, 50 μM, and 100 μM) stress environment. The results showed that exogenous P, Se supply could mitigate irreversible damage to peanut seedlings by altering the distribution of Cr in roots and aboveground, changing root conformation, and repairing damaged cells to promote growth. When the Cr concentration is 100 μM, it exhibits the highest toxicity. Compared to the control group P and Se (0 MM), the treatment with simultaneous addition of P + Se (0.5 + 6.0) resulted in a significant increase in root length and root tip number by 248.7% and 127.4%, respectively. Additionally, there was a 46.9% increase in chlorophyll content, a 190.2% increase in total surface area of the seedlings, and a respective increase of 149.1% and 180.3% in soluble protein content in the shoot and roots. In addition, by restricting the absorption of Cr and reducing the synthesis of superoxide dismutase SOD (Superoxide dismutase), CAT (Catalase), POD (Peroxidase), and MDA (Malonaldehyde), it effectively alleviates the oxidative stress on the antioxidant system. Therefore, the exogenous addition of P (0.5 MM) and Se (6.0 MM) prevented the optimal concentration of chromium toxicity to peanuts. Our research provides strong evidence that the exogenous combination of P and Se reduces the risk of peanut poisoning by Cr, while also exploring the optimal concentration of exogenous P and Se under laboratory conditions, providing a basis for further field experiments.